“JANGAN BUNUH AKU!” HUMANISME LEVINAS SEBAGAI ANTI-HUMANISME DAN KRITIK ATAS TOTALISME MODERN - Putra, Agustinus Tamtama (Forum, 2025)
This paper elaborates on the thought of Immanuel Levinas as an ethical guideline that also phenomenologically shows the ontological basis of human relations. The openness to the other and the vulnerability of human relationships are discussed in the philosophy of relationality. The author argues that the ethics that Levinas offers are truly fundamental as guidelines for practicing ethics and thus developing humanity. The literature research found that Levinas' humanism is anti-humanism. This anti-humanism is distinguished from anti-humanitarianism which actually develops humanism itself. The anti-humanism that can be explored in Levinas's ethical thought ultimately undermines modern totalism which is ontologically, epistemologically and axiologically-practically cruel to humanity.